Inhibition of human lymphokine-activated killer activity by smokeless tobacco (snuff) extract - Lindemann, R A; Park, N H (Archives of oral biology, 1988)
Chronic snuff dipping has been associated with oral cancer in man and experimental animals. Here, the effects of a water-extract of snuff on the in-vitro development of human lymphokine-activated killer (LAK) activity were examined. The snuff extract inhibited both LAK cytotoxicity and DNA synthesis in a dose-dependent fashion at concentrations of 0.125 to 2.0 per cent; above 2.0 per cent, cell viability decreased significantly. In contrast, the snuff extract had no effect on natural killer-cell cytotoxicity when incubated with fresh peripheral blood lymphocytes in a standard 4 h assay, or on LAK cytotoxicity when incubated only during the final 4 h effector phase. Lymphocyte protein synthesis was generally unaffected by the addition of this extract. Thus, a water-soluble snuff extract appears to suppress LAK activity by inhibiting DNA synthesis. Altered LAK function in the oral mucosa might permit the development of snuff-associated carcinogenesis.